Human Antibodies Neutralize Enterovirus D68 and Protect Against Infection and Paralytic Disease - Vogt, Matthew R. (Sci Immunol, 2020)
Enterovirus D68 (EV-D68) causes outbreaks of respiratory illness, and there is increasing evidence that it causes outbreaks of acute flaccid myelitis (AFM). There are no licensed therapies to prevent or treat EV-D68 infection or AFM disease. We isolated a panel of EV-D68-reactive human monoclonal antibodies that recognize diverse antigenic variants from subjects with prior infection. One potently neutralizing cross-reactive antibody, EV68–228, protected mice from respiratory and neurologic disease when given either before or after infection. Cryo-electron microscopy studies revealed that EV68–228 and another potently neutralizing antibody (EV68–159) bound around the five-fold or three-fold axes of symmetry on virion particles, respectively. The structures suggest diverse mechanisms of action by these antibodies. The high potency and effectiveness observed in vivo suggest that antibodies are a mechanistic correlate of protection against AFM disease and are candidates for clinical use in humans with EV-D68 infection.